Determinan Kinerja Karyawan Omega Computer Cabang Banyuwangi - Rahman, Arif; Yuliandari, NI Kadek (ANALISA : JURNAL MANAJEMEN DAN AKUNTANSI, 2024)
Information technology is the study of the design, implementation, development, support or management of computer information systems, particularly in hardware and software applications. This study aims to examine and analyze the effect of leadership style, incentives and work discipline on employee performance either simultaneously or partially at Omega Comp Banyuwangi.This study uses a questionnaire method and data processing using instrument test data analysis, classical assumption test, multiple regression analysis, determination test and hypothesis testing. questionnaires were distributed to 30 respondents who are employees of Omega Comp Banyuwangi. The results of this study indicate that leadership style has a partial and insignificant effect on employee performance, incentives do not have a significant effect on employee performance, work discipline has no influence and is not significant on employee performance. employee performance. So it can be concluded that the f test value shows that simultaneously leadership style, incentives and work discipline have a significant effect on employee performance.